Pemberdayaan Perempuan Rawan Sosial Ekonomi (Prse) Dalam Meningkatkan Kesejahteraan Keluarga di Kabupaten Bantul Tahun 2013-2018 - Aâ€™yun, Wina Qurratu; Faidati, Nur Faidati (ijd-demos, 2021)
AbstractThis study aims to understand the empowerment process of SocioEconomic Vulnerable Women and identify factors that influence the empowerment of socioeconomic vulnerable women in Bantul Regency. This study uses descriptive qualitative. The data were gathered through in-dept interviews and documentation. Informants include PRSE empowerment administrators, PRSE assistants, PRSE members. The results show that there has been success in the process of empowering women with socio-economic vulnerabilities in improving family welfare in Bantul Regency. This is done through training in cooking skills, making snacks, making crafts, and trading. These empowerment activities contribute through empowerment efforts so as to reduce poverty. In addition, there are factors that encourage and hinder the process of empowering women with socioeconomic vulnerabilities. The factors that drive the success of the PRSE program (1) support from family. (2) establishing good cross-sectoral relations. (3) there is a kinship relationship between the management, assistant, and members of the empowerment. (4) budget from the Regional Government, Bantul Regency Social Service especially as empowerment facilitators. Meanwhile, the inhibiting factors are (1) the low quality of Human Resources (HR) in accepting or understanding that community empowerment can support the level of welfare. (2) there is a lack of good time management of women members who are vulnerable to socio-economy in every monthly group meeting.Keywords: community empowerment, socio-economic vulnerable women, family welfareAbstrakPenelitian ini bertujuan untuk memahami proses pemberdayaan Perempuan Rawan Sosial Ekonomi (PRSE) dan mengidentifikasi faktor yang mempengaruhi pemberdayaan perempuan rawan sosial ekonomi di Kabupaten Bantul. Penelitian ini menggunakan metode penelitian kualitatif. Teknik pengumpulan data menggunakan wawancara mendalam dan dokumentasi. Informan meliputi pengurus pemberdayaan PRSE, pendamping PRSE, anggota PRSE. Hasil penelitian menunjukkan bahwa proses pemberdayaan perempuan rawan sosial ekonomi dalam meningkatkan kesejahteraan keluarga di Kabupaten Bantul cukup berhasil dilakukan. Hal tersebut dilakukan melalui kegiatan pelatihan keterampilan memasak, membuat makanan ringan, membuat kerajinan, dan berdagang. Kegiatan pemberdayaan tersebut berkontribusi terhadap penurunan angka kemiskinan. Faktor-faktor yang mendorong keberhasilan program PRSE (1) adanya dukungan dari keluarga. (2) terciptanya hubungan relasi antar lintas sektor yang baik. (3) adanya hubungan kekeluargaan antara pengurus, pendamping, dan anggota pemberdayaan. (4) anggaran dari Pemerintah Daerah, Dinas Sosial Kabupaten Bantul khususnya sebagai fasilitator pemberdayaan. Sementara itu faktor penghambatnya adalah (1) rendahnya kualitas Sumber Daya Manusia (SDM) dalam menerima atau memahami bahwa pemberdayaan masyarakat dapat menunjang tingkat kesejahteraan. (2) kurang baiknya manajemen waktu dari anggotaÂ  perempuan rawan sosial ekonomi di setiap pertemuan kelompok bulanan.Kata kunci: pemberdayaan masyarakat; perempuan rawan sosial ekonomi; kesejahteraan keluarga.